2002
DOI: 10.1677/joe.0.1730335
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lactate production and glucose transport as well as of glucose transporter 1 and lactate dehydrogenase A mRNA levels by basic fibroblast growth factor in rat Sertoli cells

Abstract: By using cultured rat Sertoli cells as a model, both the action of basic fibroblast growth factor (bFGF) on lactate production and the site of this action were studied. bFGF stimulated Sertoli cell lactate production in a dosedependent manner (basal: 7·3 0·5; 0·1 ng/ml bFGF: 7·5 0·5; 1 ng/ml bFGF: 7·5 0·6; 10 ng/ml bFGF: 10·3 1·0; 30 ng/ml bFGF: 15·2 1·5; 50 ng/ml bFGF: 15·4 1·6 µg/µg DNA). Two major sites for the action of this growth factor were identified. First, bFGF was shown to exert short-and long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Grootegoed et al showed the conversion of glucose to lactate by Sertoli cells (27). This locally produced lactate is augmented by paracrine/autocrine factors such as transforming growth factor β, epidermal growth factor, basic fibroblast growth factor, tumor necrosis factor α and interleukin 1α (28)(29)(30)(31)(32), which are involved in cell-cell communications in the testis (33). These factors target glucose uptake and total LDH activity for stimulating lactate production.…”
Section: Discussionmentioning
confidence: 99%
“…Grootegoed et al showed the conversion of glucose to lactate by Sertoli cells (27). This locally produced lactate is augmented by paracrine/autocrine factors such as transforming growth factor β, epidermal growth factor, basic fibroblast growth factor, tumor necrosis factor α and interleukin 1α (28)(29)(30)(31)(32), which are involved in cell-cell communications in the testis (33). These factors target glucose uptake and total LDH activity for stimulating lactate production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acidification of the tumour environment by lactate may account for bFGF overexpression (D'Arcangelo et al, 2000). On the other hand, a direct effect of bFGF on LDH cellular levels has been recently shown by Riera et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that both pathways might be participating in the regulation of the final biological response. Riera et al (2002) showed that increments in glucose uptake and in LDH activity are part of the mechanisms utilized by bFGF to increase lactate production. Therefore, we next analyzed the possible participation of MAPK-and PI3K/PKBsignaling pathways on the regulation of these two metabolic steps that are important contributors to the ability of a cell to increase its lactate production.…”
Section: Discussionmentioning
confidence: 99%